Developing technical training : a structured approach for developing classroom and computer-based instructional materials - Clark, Ruth Colvin (Pfeiffer essential resources for training and HR professionals., 2008)
Since it was first published almost twenty years ago, Developing Technical Training has been a reliable resource for both new and seasoned training specialists. The third edition of this classic book outlines a systematic approach called the Instructional Systems Design (ISD) process that shows how to teach technical content defined as facts, concepts, processes, procedures, and principles. Whether you teach "hard" or "soft" skills, or design lessons for workbooks or computers, you will find the best training methods in this book. Using these techniques, you can create learning environm.